2014
DOI: 10.1002/tcr.201402018
|View full text |Cite
|
Sign up to set email alerts
|

The Quantum Nature of CH···Metal Interaction: Vibrational Spectra and Kinetic and Geometric Isotope Effects of Adsorbed Cyclohexane

Abstract: The nature of C-H···M (M = metal surface) interactions is reviewed based mainly on our recent investigations of cyclohexane on Rh(111). Infrared reflection-absorption spectroscopy measurements at low temperature (∼20 K) have shown that the softened CH stretching band consists of several sharp peaks. At temperatures above 80 K, each peak is broadened, most probably by anharmonic coupling with thermally excited low-energy frustrated translational modes. The origin of fine structure in this band and its similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
(145 reference statements)
1
10
0
Order By: Relevance
“…Employing a QH approximation, in which the harmonic ZPE contributions were calculated with the molecule fixed at different distances from the surface, it could be shown that the binding energy of C 6 D 12 is smaller than that of C 6 H 12 and that C 6 D 12 lies 0.01 Å farther from the surface than C 6 H 12 , in qualitative agreement with the isotope effects previously observed experimentally [ 2 ] at the same interface. By showing that the work‐function change of the interface is very sensitive to the molecule‐surface distance, this geometrical isotope effect could be correlated with the isotope‐induced change in the work function, thus confirming the hypothesis that Koitaya, Yoshinobu, and coworkers proposed, [ 3 ] based on experimental observations. Finally, these simulations also showed that the electronic‐density rearrangement at the interface is impacted by both bond formation and the pushback effect and that the inclusion of van der Waals contributions, improve the energetics and adsorption distances.…”
Section: Resultssupporting
confidence: 82%
“…Employing a QH approximation, in which the harmonic ZPE contributions were calculated with the molecule fixed at different distances from the surface, it could be shown that the binding energy of C 6 D 12 is smaller than that of C 6 H 12 and that C 6 D 12 lies 0.01 Å farther from the surface than C 6 H 12 , in qualitative agreement with the isotope effects previously observed experimentally [ 2 ] at the same interface. By showing that the work‐function change of the interface is very sensitive to the molecule‐surface distance, this geometrical isotope effect could be correlated with the isotope‐induced change in the work function, thus confirming the hypothesis that Koitaya, Yoshinobu, and coworkers proposed, [ 3 ] based on experimental observations. Finally, these simulations also showed that the electronic‐density rearrangement at the interface is impacted by both bond formation and the pushback effect and that the inclusion of van der Waals contributions, improve the energetics and adsorption distances.…”
Section: Resultssupporting
confidence: 82%
“…[2,5] Thei mportance of alkane s-complexes in heterogeneous catalysis and even the formation of these compounds on solid surfaces is less clear compared with homogeneous systems.A common view is that alkane C À Hb ond activation on solid surfaces typically occurs via H-atom abstraction by surface radical sites. [6] Short-lived alkane s-complexes are difficult to detect on ac atalyst surface under reaction conditions but their role as precursors to alkane activation has important consequences to our understanding of possible pathways to C À Hbond cleavage in heterogeneous catalysis.Early studies using vibrational spectroscopy revealed significant redshifts of C À Hs tretch bands of alkanes upon adsorption on transition metal surfaces, [7,8] leading researchers to consider the possibility that alkanes experience dative bonding with metallic surfaces.H owever,c ontrasting interpretations have highlighted the difficulty in drawing parallels between the binding arising from alkane adsorption on metallic surfaces and the formation of organometallic alkane s-complexes. [9,10] In contrast, the binding of adsorbates on transition-metal oxide surfaces seems to more closely resemble the bonding in organometallic complexes, [11,12] suggesting the possibility of establishing clearer connections between the chemical properties of these types of compounds.I ndeed, recent studies provide evidence that the formation and facile C À Hb ond cleavage of alkane s-complexes is akey feature in the surface chemistry of late transition metal oxides that expose coordinatively unsaturated metal and oxygen atoms.…”
mentioning
confidence: 99%
“…Moreover, the structural, dynamic, and electronic properties of water are known to be heavily affected by the quantum nature of the nuclei even at room temperature [7][8][9][10][11][12][13][14] . In fact, nuclear quantum effects (NQE) have also been shown, through several experiments and a few theoretical works, to play a crucial role in the behaviour of organic adsorbates on metallic surfaces [15][16][17][18][19][20][21][22][23][24] . It is thus to be expected that both conformational entropy and nuclear quantum contributions impact the physics underlying the processes of water adsorption and dissociation on metallic surfaces.…”
Section: Introductionmentioning
confidence: 99%